Pelatihan Digital Marketing untuk Meningkatkan Penjualan Produk Pertanian Kelompok Tani Wanita Permata Indah Desa Selur - Fitra Rizal; Dhimas Haryo Prayoga; Diah Ihdini Amalia; Diah Ayu Rosanti; Endriana Nur Anggrahini; Erika Mega Wahyu Andini (Abdimas Indonesian Journal, 2022)
The Permata Indah Women Farmers Group in Selur Village was established in 2011 with the aim of empowering housewives and boosting the family economy. Activities at the Women's Farmer Group (KTW) are in the form of processing plantation products in the form of bananas into processed foods such as chips and banana sale. Since the Covid-19 pandemic began to spread in the Ponorogo Regency area, the level of sales has also decreased because the sales system still does not use social media. As a result, production activities are also stopped to avoid losses. But now, after almost 2 years of production stopping and the pandemic starting to improve, the enthusiasm of the mothers has decreased. Therefore, we have the initiative to hold a training which was attended by 20 participants with the theme of digital marketing to provide new business innovations through digital platforms. The purpose of this training is to provide knowledge about digital marketing based on social media and increase sales of women's farmer groups' products. This activity uses an asset-based community-development (ABCD) approach to optimize existing assets and potential. The end result of this activity is that the trainees can create and operate social media accounts in the form of WhatsApp Business and Instagram Business. Thus, it is hoped that it can improve the economy for the Permata Indah Women Farmer Group in Selur Village. The trainees also felt satisfied and more motivated to restart production that had stopped.